Incidence and Prognostic Factors for Legionnaires' Disease in Denmark 1993–2006. (14th August 2012) - St-Martin, G.; Uldum, S.; Mølbak, K.
Abstract : Objectives . To describe the incidence of Legionnaires' disease and factors affecting survival in Denmark from 1993 to 2006. Methods . Retrospective register study using data on episodes of Legionnaires' disease from notification forms and the National Reference Laboratory, and information on comorbidity from national registers on discharge diagnoses and mortality. Results . The average annual incidence of laboratory confirmed cases was 1.5 per 100000 people. The 30-day case fatality was 19%, ranging from 7% in travellers to 37% in hospital-acquired cases. Patients older than 60 years and patients with underlying disease were more likely-to die, as were patients infected with L. pneumophila serogroup 6. The lowest mortality was seen for L. pneumophila serogroup 1. Conclusion . Increased awareness of the disease, better diagnostics, and appropriate testing and treatment strategies are needed to improve survival. In particular, we focus on the relevance of diagnostic methods, such as polymerase chain reaction (PCR), that detect other serogroups than the urinary antigen tests used that will only reliably detect antigen from L. pneumophila serogroup 1. PCR is faster and more sensitive than culture.